Comparison of Nutritional Status Between Exsclusive Breastfeeding And Formula Milkfed In Infants 0-6 Month - Yuliana Yuliana; Glory Glory (Jurnal Kebidanan dan Kesehatan Tradisional, 2021)
Background: Malnutrion is compounded by the proliferation of processed foods like infant formula. This causes an increase in poor diets, obesity and a marked reduction in the number of mothers breastfeeding their babies. Results of a preliminary study at the Sungai Kakap Health Center on 20 Infants shows that malnutrition is higher in infants who are given formula milk than in infants who are exclusively breastfed were 4 vs 1.Aim of this study is to compare nutritional status between exclusive breastfeeding and formula milkfed. Methods: This study used a comparative analytic design. This study’s population was 39 Infants who get formula milk as a subject group at the Sungai Kakap Health Center. Sampel consist of 36 Infants exclusively breastfed (control) and 36 Infants formula milk as a subject choose by random sampling technic. The instrument used was a observational sheet and categorial sheet. The bivariate analysis used Mann Whitney Results: The test results showed a comparasion nutritional status between exclusively breastfed and formula milk (p=0,016) on Infants 0-6 month and the average ranking of the group of Infants with exclusively breastfed is higher (41.50) than the group of Infants with formula milk (31.50), but malnutrion suffered at male baby than female Conclusion: Used of varied and interesting tools about exclusive breastfeeding and counseling about best nutrition for Infants needs to be increased.